Penerapan Program Kesehatan dan Keselamatan Kerja dalam Aktivitas Kerja Coal Hauling di PT. XYZ - Rembulan, Glisina Dwinoor; Sumakud, Christovel Ridgel Ronaldo (Universitas Medan Area, 2024)
The implementation of an occupational health and safety (K3) program can be an effort for mining companies to make efforts to prevent accidents in mining work activities such as coal hauling. Based on this, the purpose of this study was to analyze the implementation of K3 (occupational health and safety) on coal hauling activities by PT. XYZ with HAZOP and HIRARC methods. The research was carried out using data collection methods such as interviews, observations, and document studies. Furthermore, the data were analyzed using the HAZOP and HIRARC methods, which are data analysis methods that aim to determine the potential hazards that exist in mining work activities. The results showed that through the HAZOP analysis showed that there were 12 sources of danger in 5 work activities in the Coal hauling section. These 12 hazard sources are divided into 4 hazard categories with 56% high risk, 24% moderate risk, 15% extreme conditions, and 5% low risk. Based on this, it can be seen that the potential hazard by causing work accidents is quite significant. Meanwhile, the HIRARC analysis shows that there are 6 sources of danger with 9 potential work accidents which are divided into 4 categories of hazards as much as 51% high risk 4 potential risks, 21% extreme risk with 1 high value potential risk, 18% low risk with 3 potential risks, and 10% medium risk with 1 potential hazard. This potential and source of danger has and will continue to allow for the occurrence of losses, both material and physical injury to employees.